ERP Database Migration From On-Promise To The Cloud: An Iterative Methodology - Majda EL MARIOULI, Jalal LAASSIRI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
One of the most complex and demanding processes of migration from one or multiple legacy systems to an ERP system is database migration. Data migration is seen as a major research challenge in cloud environments. There are many factors to take in consideration on the migration process, there factors include: Data migration costs, data quality, duration, data volume, system performance, data retention and the enablement of new system functionality are all factors to take in consideration on the migration process. There are multiple cases to migrate data into an ERP Cloud, such as migrating and conversion from on-premise ERP to Cloud ERP for homogeneous or heterogeneous databases or from non-ERP systems to a Cloud ERP systems. Through this article we present different methodologies and approaches for data migration from legacy systems to modern systems. In addition we introduce an iterative methodology to migrate database from legacy ERP systems to ERP cloud using ETL